Let's solve the expression step-by-step:
The expression we need to evaluate is \((2 + 5) - \frac{16}{(2)^3}\).
-
Start by solving the parentheses: \[ 2 + 5 = 7 \]
-
Next, evaluate \((2)^3\): \[ (2)^3 = 2 \times 2 \times 2 = 8 \]
-
Now substitute these results back into the expression: \[ 7 - \frac{16}{8} \]
-
Calculate \(\frac{16}{8}\): \[ \frac{16}{8} = 2 \]
-
Now substitute this back into the expression: \[ 7 - 2 \]
-
Finally, perform the subtraction: \[ 7 - 2 = 5 \]
Thus, the final result is \(\boxed{5}\).